2015
DOI: 10.1111/camh.12107
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting standardized and idiographic outcome measures in CAMHS: what does change mean and how does it relate to functioning and experience?

Abstract: Background: Patient Reported Outcome Measures (PROMs) are increasingly being used in Child and Adolescent Mental Health Services (CAMHS). The aim of this research was to explore change in standardized and idiographic outcome measures in CAMHS using naturalistic, routinely collected data. Method: We explored change in psychosocial difficulties and impact on daily life as evaluated by a broad standardized measure, the Strengths and Difficulties Questionnaire (SDQ) (Goodman, 1997, J. Child Psychol. Psychiatry, 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
67
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 40 publications
9
67
0
1
Order By: Relevance
“…Young people are asked to identify up to three goals for therapy and, at each of the time points, rate on a 0–10 scale how much progress they feel they have made towards that goal. The GBO tool has shown convergent validity against measures of functioning and psychosocial difficulties, and acceptable levels of internal consistency (α = .71, Edbrooke‐Childs, Jacob, Law, Deighton, & Wolpert, ). The internal consistency in the present sample was .83 at 12 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Young people are asked to identify up to three goals for therapy and, at each of the time points, rate on a 0–10 scale how much progress they feel they have made towards that goal. The GBO tool has shown convergent validity against measures of functioning and psychosocial difficulties, and acceptable levels of internal consistency (α = .71, Edbrooke‐Childs, Jacob, Law, Deighton, & Wolpert, ). The internal consistency in the present sample was .83 at 12 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on outcomes in naturalistic settings showed that children and adolescents with psychosocial problems who receive treatment experience some improvement, meaning less psychosocial problems were measured with SDQ at follow‐up (Deighton et al., ; Edbrooke‐Childs, Jacob, Law, Deighton, & Wolpert, ). In addition, another study showed a significant relationship between the number of treatment sessions (more than 8) and improvement in psychiatric symptoms (measured with the Child and Adolescent Psychiatric Assessment) at follow‐up (Angold, Costello, Burns, Erkanli, & Farmer, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence of its psychometric properties is limited, and it has shown a strong negative skew at endpoint (Cooper, Stewart, Sparks, & Bunting, ). Goal‐based outcome measures are also strength‐oriented and, as idiographic measures, have the advantage of being adaptable to a wide range of individual concerns (Edbrooke‐Childs, Jacob, Law, Deighton, & Wolpert, ). As tools for service evaluation, however, they have the disadvantage of being more difficult to interpret, and compare, at the group level.…”
Section: Introductionmentioning
confidence: 99%